Answer:
1
Step-by-step explanation:
Because once you know the unknown you can plug it into the equation so now its 11-10 which equals 1
Answer:
x=11
Step-by-step explanation:
5x+13=9x-31
subtract 9 from both sides.
-4x+13=-31
you want to isolate the x value so subtract 13 from both sides.
-4x=-44
now divide both sides by -4.
x=11
Answer:
Step-by-step explanation:
Given
![P = \frac{3 - 2t}{4 + t}](https://tex.z-dn.net/?f=P%20%3D%20%5Cfrac%7B3%20-%202t%7D%7B4%20%2B%20t%7D)
Required
Make t the subject
![P = \frac{3 - 2t}{4 + t}](https://tex.z-dn.net/?f=P%20%3D%20%5Cfrac%7B3%20-%202t%7D%7B4%20%2B%20t%7D)
Cross Multiply
![P * (4 + t) = 3 - 2t](https://tex.z-dn.net/?f=P%20%2A%20%284%20%2B%20t%29%20%3D%203%20-%202t)
![4p + tp = 3 - 2t](https://tex.z-dn.net/?f=4p%20%2B%20tp%20%3D%203%20-%202t)
Collect Like Terms
![tp + 2t = 3 - 4p](https://tex.z-dn.net/?f=tp%20%2B%202t%20%3D%203%20-%204p)
Factorize:
![t(p+2) = 3 - 4p](https://tex.z-dn.net/?f=t%28p%2B2%29%20%3D%203%20-%204p)
Make t the subject
![t = \frac{3 - 4p}{p + 2}](https://tex.z-dn.net/?f=t%20%3D%20%5Cfrac%7B3%20-%204p%7D%7Bp%20%2B%202%7D)